Thematic linking in Hausa asymmetric coordination - Linda Schwartz (LibraryPress@UF, 1989)
This paper investigates "asymmetric coordination" in Nigerian Hausa. A range of constructions is presented in which asymmetric coordination occurs, and their syntactic and semantic properties are established. A "regularizing" analysis is considered, in which asymmetric coordination is represented as a symmetric coordination headed by an empty category, but this is rejected due to the exceptional distributional properties which would have to be assumed for the construction. An interpretive analysis is proposed which has the effect of incorporating the feature information of an independent NP marked by a "linker" into a dependent plural argument, and symmetric and asymmetric coordination are distinguished as involving interpretive operations of set union and set unification, respectively.